Team Hyena Puppet: An Interdisciplinary Approach to Making and Teaching Science Through Art. Issue 1 (3rd April 2019) - Trommer-Beardslee, Heather; Dasen, Ann; Pangle, Wiline; Batzner, Jay
ABSTRACT: In 2016, professors representing Biology, Dance, Music, and Theatre and dance program students created Dunes, a performance piece that depicts the ecological succession of Michigan's sand dunes. The process used to make this work is a direct representation of the steps that Team Hyena Puppet, a collective of teaching artists and scientists, takes in their science-based art collaborations, which are used to reflect on and depict scientific research and simultaneously teach student participants and audience members science through the performing arts.